The promoter of the latency-associated transcripts of herpes simplex virus type 1 contains a functional cAMP-response element: role of the latency-associated transcripts and cAMP in reactivation of viral latency. - Leib, D A (1991)
A 203-base-pair sequence 5' of the latency-associated transcripts (LATs) of herpes simplex virus type 1 contains a 7-base consensus sequence TGCGTCA that is identical to the cAMP-response element of the proenkephalin gene. This consensus sequence is at -38 relative to the putative 5' end of the LATs with a TATA box at the -24 position. In transient chloramphenicol acetyltransferase assays in rat pheochromocytoma (PC12) cells, this enhancer region stimulated gene expression up to 3-fold in the presence of dibutyryl cAMP, forskolin, nerve growth factor, or phorbol 12-myristate 13-acetate. Mutation of the cAMP-response element to TGCG-CAA resulted in a 4-fold reduction of basal activity and a complete loss of inducible stimulation. In DNA gel retardation assays, purified cAMP-response element-binding protein and a nuclear protein from PC12 cells were shown to bind specifically to this element. Furthermore, it was demonstrated that the reactivation of wild-type herpes simplex virus type 1 from dissociated latently infected murine trigeminal ganglia was significantly accelerated (P less than 0.005) by the addition of cAMP analogs or adenylate cyclase activators. However, these reagents did not accelerate reactivation of a deletion mutant that lacks the putative cAMP-response element-containing promoter region, transcriptional start site, and 1015 base pairs of the LATs. These studies demonstrate that the promoter region of the LATs contains a functional cAMP-response element and that expression of the LATs is likely controlled by second messenger signal transduction and imply a role for cAMP in triggering viral reactivation.